Danze rituali nella Roma arcaica. Tra processioni saliari e Lusus Troiae (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2019)
The analysis of the sources about ritual dances in archaic Rome confirms that these rituals  belonged to the Roman cultural and religious facies since the beginning. This paper focuses on the Salian priesthood, on the possible route they followed during their processions and their movements. Furthermore, several points of contacts between the Salian dance and the Lusus Troiae described by Vergil are highlighted through the study of the testimonies, including those concerning Theseus’s γέρανος.
Keywords: ritual dance; Rome; armed dance; Salii; Lusus Troiae; Tragliatella; γέρανος